Origin of surface layer on common substrates for functional material films probed by ellipsometry - Belyaeva, A.I.; Galuza, A.A.; Kudlenko, A.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
A multiple angle ellipsometric method is used to investigate thin film layers on common substrates (gadolinium gallium garnet-GGG, sapphire-Al₂O₃, and glass ceramic sitall) for functional material films. The method evaluates fundamental optical constants and thicknesses of the layers. Dielectric functions for the surface layers on such kind of plates have been determined. Coincidence up to the third decimal point in refractive index value (nf) was shown. Errors for the thickness of surface layer (df) is not more than 3 %. It is shown that the dielectric properties of microscopically rough layers of thickness ~10-45 nm can be accurately modeled in the homogeneous thin layer approximation. The thickness and origin of the surface layer on substrates are found out. Experimental data analysis allows to make some conclusions concerning the origin of this layer. It is a specific amorphous damaged layer that remains after taking out stressed surface layer via chemical polishing. The corrosion processes on glass ceramic seems to be very similar to those occurring on GGG and sapphire single crystals.